Impairment of lagging strand synthesis triggers the formation of a RuvABC substrate at replication forks - Flores, Maria-Jose (Oxford University Press, 2001)
The holD gene codes for the ψ subunit of the Escherichia coli DNA polymerase III holoenzyme, a component of the γ complex clamp loader. A holD mutant was isolated for the first time in a screen for mutations that increase the frequency of tandem repeat deletions. In contrast to tandem repeat deletions in wild-type strains, deletion events stimulated by the holD mutation require RecA. They do not require RecF, and hence do not result from the recombinational repair of gaps, arguing against uncoupling of the leading and lagging strand polymerases in the holD mutant. The holD recBC combination of mutations is lethal and holD recBts recCts strains suffer DNA double-strand breaks (DSBs) at restrictive temperature. DSBs require the presence of the Holliday junction-specific enzymes RuvABC and are prevented in the presence of RecBCD. We propose that impairment of replication due to the holD mutation causes the arrest of the entire replisome; consequently, Holliday junctions are formed by replication fork reversal, and unequal crossing over during RecA- and RecBCD-mediated re-incorporation of reversed forks causes the hyper-recombination phenotype.